ANALISIS TRANFER PRICING DALAM LENDING ACTIVITIES BANKING DENGAN MENGGUNAKAN ARM’S LENGTH PRINCIPLE - Deni D. Kesa; Erwin Harinurdin; Asti Setiawati (Jurnal Vokasi Indonesia, 2015)
AbstractRegulatory motivation is often done by some of the industries associated with strict regulatory supervision, such as banks and insurers. It is associated with one of them in fulfillment of the Capital Adequacy Ratio (CAR) and Solvency Margin ratio which can create incentives for management to make earnings management in the interest of regulators. From previous studies found indications that the bank's management to practice earnings management in order to meet regulatory (regulator) and the investor.API is one of the policy on sole ownership in Indonesian banks (Single Presence Policy). Because these policies will have consequences that could affect the existence of banks in Indonesia and banking services. It is necessary for research on banking transactions of the party - affiliated parties in the use of the principles of fairness and the predominance of business (arm's length principle). The method used in this research is descriptive analysis and the results will be analyzed qualitatively. Keywords: Principles of fairness and the predominance of business, price comparison method, banking.